(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of the study is to determine the level of effectiveness of online marketing to the customer's loyalty to JCJ Seat Zone General Upholstery in Quezon City in terms of age, gender, and employment status. The result of the study reveals that the majority of respondents are employed between the ages of 21 and 30 years old; the majority of female respondents answered that the desired fabric and materials are followed, and the majority of male respondents answered that they communicate effectively and imparts thorough knowledge about the offered product and services in terms of brand positioning. In terms of quality expectation, the majority of female respondents answered that providing excellent service to the customer, knowledge, courtesy of employees, and their ability to convey trust and confidence are ethical, well-managed, and accurate services. The majority of male respondents answered that providing excellent service to the customer, products, and services at the given time, knowledge and courtesy of employees, and their ability to convey trust and confidence are ethical. In terms of product durability, the majority of female respondents answered that the quality of the product is superb and can go through frequent usage (daily usage). The majority of male respondents answered that they can go through frequent usage (daily usage). “How do females and males assess the level of effectiveness of online marketing to the customer's loyalty in terms of brand positioning, quality expectation, and product durability? Female “Strongly Agree” and male “Agree.” The problems encountered by JCJ Upholstery are delayed support response, lack of skills and experience in the field of marketing, and being inactive on social media channels. The researchers recommend to the owner of JCJ General Upholstery to help them improve and attract more customers; they should be active on social media by appointing skilled employees when it comes to online marketing techniques and strategy.